Ayta’s Indigenous Healthcare Practices: A Descriptive-Qualitative Study - Fabrigas, Yves Clark; Maniago, Jestoni D. (European Scientific Journal, ESJ, 2018)
This descriptive qualitative study aimed to describe the healthcare practices of Aytas at Lakas Pamayanan, Philippines. The researchers who were culturally immersed to the community involved 100 Aytas of LAKAS Pamayanan who comprised of tribal leaders, tribal healers and tribal members. Ethical approval was secured from appropriate agencies and the participants provided their consent to conduct this research. Research techniques employed were interviews, non-participant observation and video documentation. For almost three years of cultural immersion and data gathering, the following insights were revealed: (1) Aytas still believed that sickness was caused by weather, ‘kamana’ and supernatural forces of nature. (2) The diversity of herbal medicines and its preparation have cultural importance to Aytas’ different stages of life and different healing practices. (3) Aytas still used natural supplements such as bamboo blades for cutting umbilical cords and ‘bigkis’ for Ayta women who have just given birth. (4) There were not much of healthcare practices during puberty, adolescence and adulthood except for menstrual beliefs and circumcision because these part of their lives was concerned to their cultural views. (5) Aytas perceived that technology, media and modernization as well as the medical missions and outreach programs disconnect them from their cultural identity. (6) Aytas have shown some reception to public health programs such as hygiene. Aytas were able to preserve their cultural healthcare practices up to this time. It was recommended to develop a culturally-congruent nursing care model that will streamline evidence-based practice for indigenous groups in the Philippines.